2014
DOI: 10.1073/pnas.1410530111
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-induced lipolysis causes mTOR complex dissociation and inhibits glucose uptake in adipocytes

Abstract: Anabolic and catabolic signaling oppose one another in adipose tissue to maintain cellular and organismal homeostasis, but these pathways are often dysregulated in metabolic disorders. Although it has long been established that stimulation of the β-adrenergic receptor inhibits insulin-stimulated glucose uptake in adipocytes, the mechanism has remained unclear. Here we report that β-adrenergic-mediated inhibition of glucose uptake requires lipolysis. We also show that lipolysis suppresses glucose uptake by inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…mTORC2 activity in hepatocytes is inhibited by overexpression of glycerol-3-phosphate acyltransferase-1 (Gpat1), and mTORC2 can be disrupted in vitro by treatment with preferred Gpat1 substrates (Zhang et al, 2012). Similar recent studies have found that lipolytic products produced either in vivo or in vitro can disrupt mTORC2, although the precise lipid or lipids that mediate this effect have not been identified (Mullins et al, 2014). Conversely, mTORC2 activity can be stimulated by expression of fatty acid elongase-5 (Elovl5), or by treatment of cells with the Elovl5 substrate palmitoleic acid (Tripathy and Jump, 2013).…”
Section: Regulation Of Mtorc1 and Mtorc2 By Nutrient And Endocrine Simentioning
confidence: 66%
“…mTORC2 activity in hepatocytes is inhibited by overexpression of glycerol-3-phosphate acyltransferase-1 (Gpat1), and mTORC2 can be disrupted in vitro by treatment with preferred Gpat1 substrates (Zhang et al, 2012). Similar recent studies have found that lipolytic products produced either in vivo or in vitro can disrupt mTORC2, although the precise lipid or lipids that mediate this effect have not been identified (Mullins et al, 2014). Conversely, mTORC2 activity can be stimulated by expression of fatty acid elongase-5 (Elovl5), or by treatment of cells with the Elovl5 substrate palmitoleic acid (Tripathy and Jump, 2013).…”
Section: Regulation Of Mtorc1 and Mtorc2 By Nutrient And Endocrine Simentioning
confidence: 66%
“…Thyroid hormones and leptin can improve insulin sensitivity (Lin et al, 2002; Lin and Sun, 2011; Petersen et al, 2002; Sivitz et al, 1997), and they have been linked with increased BAT activity (Chondronikola et al, 2014; Collins et al, 1996). These results suggest that BAT activation may (directly or indirectly) abolish the negative effect of cold-induced increase in catecholamines in adipose tissue insulin sensitivity (Mullins et al, 2014). …”
Section: Resultsmentioning
confidence: 92%
“…For example, cAMP promotes mTORC1 activity in thyroid cells (39) and β-cells (40), whereas it disrupts both mTORC1 and mTORC2 in MEFs (41) and, via the downstream effects on lipolysis, in white adipocytes (42). In brown adipocytes, β-adrenergic signaling promotes translocation of GLUT1 to the plasma membrane in an mTORC2-dependent, but cAMP-independent, manner, whereas in muscle cells, β-adrenergic signaling activates mTORC2 via PKA.…”
Section: Discussionmentioning
confidence: 99%